PEMBONCENGAN NAMA MEDIA MASSA TERHADAP TABLOID MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS - Kirana Wibowo (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTBy lifting the title essay "PEMBONCENGAN NAME OF TABLOID MEDIA BY LAW NUMBER 40 OF 1999 ON THE PRESS".to know how the mass media responsibility bum tabloids and harmful to others and measures taken by the injured party in the event of contamination honor or reputation by the mass media.To be able to carry out the functions of the national press that is free and responsible, requiring the press law as legal rules that define the conditions, rights and obligations of the press. Which has been regulated in Law Number 40 of 1999 on the Press.If the injured party or are not satisfied, then the injured party filed a lawsuit to District Court and after the issuance of the press is addressed and contains a refutation or explanation for what harms it. Claims for compensation by the injured party who felt the name used by the media the press, so that the journalists as an officer in spreading the news to the news media can respond for his mistakes and be able to receive claims for compensation of the injured party that, if indeed it is proven guilty ,The responsibility of the mass media of the name of the harm others demanded that, if the injured party is actually not to do anything that has been reported in the mass media. The responsibility of the mass media or news media on the wrong deeds of news or news that harm others, we can sue for damages on its behalf are used in accordance with the decision of District Court judge and in accordance with Article 1365 of the Civil Code for damages that have determined it.Keywords: Pemboncengan name of the mass media, the Law number 40 of 1999, claims for compensation.